2001
DOI: 10.1037/1099-9809.7.4.343
|View full text |Cite
|
Sign up to set email alerts
|

Cultural value similarities and differences among Asian American ethnic groups.

Abstract: Using data on 570 Chinese, Filipino, Korean, and Japanese American college students from 3 previous studies (1 published [B. S. K. Kim, D. R. Atkinson, & P. H. Yang, 1999] and 2 unpublished [B. S. K. Kim, 1999; E. C. Wong, B. S. K. Kim, N. W. S. Zane, I. J. Kim, & J. S. Huang, 1999]), the authors subjected 22 items constituting 6 value dimensions of the Asian Values Scale (AVS; B. S. K. Kim et al., 1999) to the following structural equation modeling procedures: confirmatory factor analysis, factorial invarianc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
175
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 194 publications
(181 citation statements)
references
References 27 publications
3
175
0
Order By: Relevance
“…These results support the Rasch analysis requirement for unidimensionality. It is important to note that although Kim et al (1999) reported a six-factor structure for the AVS, a subsequent study by Kim, Yang, Atkinson, Wolfe, and Hong (2001) found that AVS items were best represented by a hierarchical structure with a unidimensional general Asian values factor on the second order followed by six factors on the first order.…”
Section: Discussionmentioning
confidence: 99%
“…These results support the Rasch analysis requirement for unidimensionality. It is important to note that although Kim et al (1999) reported a six-factor structure for the AVS, a subsequent study by Kim, Yang, Atkinson, Wolfe, and Hong (2001) found that AVS items were best represented by a hierarchical structure with a unidimensional general Asian values factor on the second order followed by six factors on the first order.…”
Section: Discussionmentioning
confidence: 99%
“…The continuous primary theme or value in social structure among Chinese throughout history has been the centrality of the family (Chin, 1996;Kim, Yang, Atkinson, Wolfe, & Hong, 2001;Tong & Spicer, 1994). It is considered shameful for individuals (even children) if the family is dissolved for any reason (e.g., divorce, parental death).…”
Section: Barriers For Grief Among Aids Orphans In Chinamentioning
confidence: 99%
“…My review of the literature has contributed to several hypotheses. In addition, because most of the research in this area has focused on adult populations (Hyman, Vu, & Beiser, 2000) and few have explored specific Asian groups (Chiu & Ring, 1998) in spite of differences across Asian American ethnic groups (B. S. K. Kim, Yang, Atkinson, Wolfe, & Hong, 2001), this study centered on Chinese, Korean, and Japanese junior high and high school students.…”
mentioning
confidence: 99%